PERANAN PENGHARAPAN DALAM PENGAMBILAN KEPUTUSAN PENENTUAN WAKTU JATUH TEMPO DEPOSITO DAN HUBUNGAN ANTAR SUKU BUNGA DEPOSITO DENGAN JATUH TEMPO YANG BERBEDA - Maryatmo, R (JURNAL BISNIS STRATEGI, 2007)
The research is dedicated to investigate the role of expectation to the a/location of assets, especially to time deposite assets with different maturity. The transmision among time deposite with different maturity is through the interest differential. The equilibrium condition of the allocation of time deposite assets with different maturity is what so called with term structure. Testing the equilibrium condition of term structure means reveals the perfectness of the market, and perfectness of the information. Perfectness of the information on the term structure implies that interest rate is market determined, and agents perfectly learn from the market and formulate their expectation, and in return it influences the market. Important information which is considered by the agents to reformulate their expectation is inflation rate. Agents have long memory on inflation information. Six or seven month information on inflation rate is examined by the agents in order to determine the allocation of their time deposite assets with different maturity.